RvD1 improves resident alveolar macrophage self-renewal via the ALX/MAPK14/S100A8/A9 pathway in acute respiratory distress syndrome - Yang Ye; Qian Yang; Jinling Wei; Chenxi Shen; Haixing Wang; Rong Zhuang; Yuan Cao; Yajun Ding; Haoran Xu; Shuyang Xiang; Hongxia Mei; Zhongwang Li; et al. (Journal of Advanced Research)
Introduction: Acute respiratory distress syndrome (ARDS) is a pulmonary inflammatory process primarily caused by sepsis. The resolution of inflammation is an active process involving the endogenous biosynthesis of specialized pro-resolving mediators, including resolvin D1 (RvD1). Resident alveolar macrophages (RAMs) maintain pulmonary homeostasis and play a key role in the resolution phase. However, the role of RAMs in promoting the resolution of inflammation by RvD1 is unclear. Objectives: Here, we investigated the mechanisms of RvD1 on regulating RAMs to promote the resolution of ARDS. Methods: Mice were administered lipopolysaccharide and/or Escherichia coli via aerosol inhalation to establish a self-limited ARDS model. Then, RvD1 was administered at the peak inflammatory response. RAMs self-renewal was measured by flow cytometry, RAM phagocytosis was measured by two-photon fluorescence imaging. In addition, plasma was collected from intensive care unit patients on days 0–2, 3–5, and 6–9 to measure RvD1 and S100A8/A9 levels using triple quadrupole/linear ion trap mass spectrometry. Results: RAMs were found to play a pivotal role in resolving inflammation during ARDS, and RvD1 enhanced RAM proliferation and phagocytosis, which was abrogated by a lipoxin A4 receptor (ALX, RvD1 receptor) inhibitor. Both primary RAMs transfected with rS100A8/A9 and/or S100A8/A9 siRNA and S100A9-/- mice (also deficient in S100A8 function) showed higher turnover and phagocytic function, indicating that RvD1 exerted its effects on RAMs by inhibiting S100A8/A9 production in the resolution phase. RvD1 reduced S100A8/A9 and its upstream MAPK14 levels in vivo and in vitro. Finally, in the patients, RvD1 levels were lower, but S100A8/A9 levels were higher. Conclusions: We propose that RvD1 improved RAM self-renewal and phagocytosis via the ALX/MAPK14/S100A8/A9 signaling pathway. Plasma RvD1 and S100A8/A9 levels were negatively correlated, and associated with the outcome of sepsis-induced ARDS.